Validating the Mild Behavioral Impairment Checklist in a Cognitive Clinic: Comparisons With the Neuropsychiatric Inventory Questionnaire. (March 2023) - Hu, Sophie; Patten, Scott; Charlton, Anna; Fischer, Karyn; Fick, Gordon; Smith, Eric E.; Ismail, Zahinoor
Objective: To compare the utility of the Mild Behavioral Impairment-Checklist (MBI-C) and Neuropsychiatric Inventory Questionnaire (NPI-Q) to capture NPS in subjective cognitive decline (SCD), mild cognitive impairment (MCI), and dementia. Methods: In this cross-sectional memory clinic study, linear regression models compared MBI-C (n = 474) and NPI-Q (n = 1040) scores in relation to Montreal Cognitive Assessment (MoCA) score. Results: MBI prevalence was 37% in subjective cognitive decline, 54% in mild cognitive impairment, and 62% in dementia. Worse diagnostic status was associated with higher MBI-C and NPI-Q score ( P < .001), lower MoCA ( P < .001), and greater age ( P < .001). Higher MBI-C (β −.09; 95% CI −.13, −.05) and NPI-Q (β −.17; 95% CI −.23, −.10) scores were associated with lower MoCA scores, with psychosis most strongly associated (β −1.11; 95% CI −1.56, −.65 vs β −1.14; 95% CI −1.55, −.73). Conclusions: The MBI-C captures global and domain-specific NPS across cognitive stages. Both the MBI-C and NPI-Q have utility in characterizing NPS.